Analysis of Taxpayer Compliance in Paying Motor Vehicle Taxes with the Fraud Hexagon Model - Tarigan, Krisnawati; Margareta, Natalia (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
Tax is one of the largest incomes owned by Indonesia, one of which is Motor Vehicle Tax. In 2020, the number of motorized vehicles recorded was 20,221,821 motorized vehicles. However, in the reporting process, there are still many taxpayers who have not carried out their responsibilities and obligations. In this study, the researcher uses the Fraud Hexagon model which is used to analyze what factors affect taxpayer compliance in paying motor vehicle taxes in the West Jakarta area. The variables used in this research are Stimulus, Opportunity, Rationalization, Capability, Ego (arrogance), and Collusion. This study uses the SEM model and is processed using SMART PLS. The sample of this study was 182 taxpayer respondents who have motorized vehicles in the West Jakarta area. The results of this study found that the factors that affect taxpayer compliance in paying motor vehicle taxes in the West Jakarta area are influenced by Opportunity and Rationalization. These two variables have a significant influence on taxpayer compliance.